Versatile iron–catechol-based nanoscale coordination polymers with antiretroviral ligand functionalization and their use as efficient carriers in HIV/AIDS therapy. (3rd December 2018) - Solórzano, Rubén; Tort, Olivia; García-Pardo, Javier; Escribà, Tuixent; Lorenzo, Julia; Arnedo, Mireia; Ruiz-Molina, Daniel; Alibés, Ramon; Busqué, Félix; Novio, Fernando
Abstract : Iron-based nanoscale coordination polymers as novel drug delivery systems for efficient HIV/AIDS therapy. Abstract : A novel chemical approach integrating the benefits of nanoparticles with versatility of coordination chemistry is reported herein to increase the effectiveness of well-known HIV antiretroviral drugs. The novelty of our approach is illustrated using a catechol ligand tethered to the known antiretroviral azidothymidine (AZT) as a constitutive building block of the nanoparticles. The resulting nanoscale coordination polymers (NCPs) ensure good encapsulation yields and equivalent antiretroviral activity while significantly diminishing its cytotoxicity. Moreover, this novel family of nanoparticles also offers (i) long-lasting drug release that is dissimilar inside and outside the cells depending on pH, (ii) triggered release in the presence of esterases, activating the antiviral activity in an on–off manner due to a proper chemical design of the ligand and (iii) improved colloidal stabilities and cellular uptakes (up to 50-fold increase). The presence of iron nodes also adds multifunctionality as possible contrast agents. The present study demonstrates the suitability of NCPs bearing pharmacologically active ligands as an alternative to conventional antiretroviral treatments.